2002
DOI: 10.1590/s0103-90162002000300018
|View full text |Cite
|
Sign up to set email alerts
|

Variability of soybean germplasm in relation to phosphorus uptake and use efficiency

Abstract: Plant efficiency for phosphorus uptake and utilization may contribute to improve crop yield potential in situations of low P availability. Twenty nine soybean [Glycine max (L.) Merr.] cultivars were evaluated and classified in relation to the response to phosphorus (P) levels in nutrient solution. P uptake and use efficiency were estimated by the variables: shoot and root dry matter (DM) yield, P-concentrations and contents in plant parts and P-efficiency index (EI). The experiment was conducted in a greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 12 publications
1
9
0
2
Order By: Relevance
“…It is well-documented that soybean genotypes differ greatly in adaptive mechanisms to P deficiency stress (Furlani et al 2002;Wang et al 2004). Some investigators have reported that P efficiency had, as most agronomic traits, shown continuous phenotype distributions, and was a typical quantitative trait (Chaubey et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-documented that soybean genotypes differ greatly in adaptive mechanisms to P deficiency stress (Furlani et al 2002;Wang et al 2004). Some investigators have reported that P efficiency had, as most agronomic traits, shown continuous phenotype distributions, and was a typical quantitative trait (Chaubey et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…One whole plant NUE study from semiarid grassland in northern China was conducted by Yuan et al, (2006 (Furlani and Furlani, 1988;Ciarelli et al, 1998;Spehar & Souza, 1999). In addition, these non destructive techniques might be useful for those species which have low germplasm availability in nature (Furlani et al, 2002). Woody perennials exhibit a characteristic time course of phosphorus acquisition and internal P redistribution during their life cycle (Fageria et al, 2011 and.…”
Section: -mentioning
confidence: 99%
“…Intra‐species differences for PAE and PUE are well known for different grain legumes and cereals. Large genotypic differences in respect of PAE and PUE were reported for soybean ( Glycine max L.; Furlani et al, 2002; Jemo et al, 2006), cowpea ( Vigna unguiculata L.; Sanginga et al, 2000; Nwoke et al., 2007), common bean ( Phaseolus vulgaris L.; Vadez et al., 1999), faba bean ( Vicia faba L.; Stelling et al, 1996; Daoui et al, 2012), and wheat ( Triticum aestivum L.; Sepehr et al, 1999; Manske et al, 2001, 2002; Korkmaz et al, 2009). Therefore, an important agronomic strategy to improve P nutrition of crops is through selection of P‐efficient varieties.…”
Section: Introductionmentioning
confidence: 96%